2017
DOI: 10.2169/internalmedicine.56.7625
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Peripherally Inserted Central Venous Catheter in Patients with Hematologic Diseases

Abstract: Objective Although use of the peripherally inserted central venous catheter (PICC) has become increasingly common, there are few reports of PICCs used for patients with hematologic diseases. In this study, we analyzed the safety of PICC placement in patients with hematologic diseases where PICCs had been placed to perform blood collection, blood transfusion, drug administration, and hematopoietic stem cell transplantation. Methods This study included 142 PICCs placed in 95 patients managed at our department f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
3
20
1
2
Order By: Relevance
“…An ultrasound-guided insertion may also reduce the incidence of PICC-related deep vein thrombosis due to reduced blood vessel damage at the time of puncture. 16 In the present study, deep vein thrombosis occurred in only two cases placed from the basilica vein. Both patients were successfully treated with only the administration of an oral anticoagulant because the embolus was small.…”
Section: Discussioncontrasting
confidence: 45%
“…An ultrasound-guided insertion may also reduce the incidence of PICC-related deep vein thrombosis due to reduced blood vessel damage at the time of puncture. 16 In the present study, deep vein thrombosis occurred in only two cases placed from the basilica vein. Both patients were successfully treated with only the administration of an oral anticoagulant because the embolus was small.…”
Section: Discussioncontrasting
confidence: 45%
“…Several reports have addressed the usefulness of PICCs in the context of malignancy, neuromuscular disease, or hematologic disease (Hashimoto et al, 2017;Juntas-Morales et al, 2017;Park et al, 2016). In addition, previous research has shown that PICC insertion is a relatively low-risk procedure compared with CVC insertion (Brass et al, 2015;Saugel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Morano SG et al also carried out research in patients with hematological malignancies with 7.7 % CLABSI and 2.6 % catheter-related thrombosis [14]. 18.9% CLABSI was reported in Yoshinori H et al study [15]. Harter C et al reported 7.7% incidence of phlebitis [16].…”
Section: Incidence and Risk Factors Of Picc-related Complicationsmentioning
confidence: 98%